2015
DOI: 10.3389/fpsyg.2015.01230
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of working memory training with individuals with intellectual disabilities – a meta-analytic review

Abstract: Working memory (WM) training has been increasingly popular in the last years. Previous studies have shown that individuals with intellectual disabilities (ID) have low WM capacity and therefore would benefit by this type of intervention. The aim of this study was to investigate the effect of WM and cognitive training for individuals with ID. The effects reported in previous studies have varied and therefore a meta-analysis of articles in the major databases was conducted. Inclusion criteria included to have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 52 publications
3
32
0
5
Order By: Relevance
“…Working memory, an ability to maintain and manipulate information for a short period of time (Miyake & Shah, ), has been reported to be trainable (Danielsson, Zottarel, Palmqvist, & Lanfranchi, ). However, only a limited number of studies have explored the neural mechanism for working memory training effect (Beatty et al, ; Dahlin, Neely, Larsson, Bäckman, & Nyberg, ; Schweizer, Grahn, Hampshire, Mobbs, & Dalgleish, ).…”
Section: Introductionmentioning
confidence: 99%
“…Working memory, an ability to maintain and manipulate information for a short period of time (Miyake & Shah, ), has been reported to be trainable (Danielsson, Zottarel, Palmqvist, & Lanfranchi, ). However, only a limited number of studies have explored the neural mechanism for working memory training effect (Beatty et al, ; Dahlin, Neely, Larsson, Bäckman, & Nyberg, ; Schweizer, Grahn, Hampshire, Mobbs, & Dalgleish, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the MBID-group report improvements in short-term memory (STM) and working memory (WM) as well as in academic achievements [4, 5]. A recent meta-analytic review revealed a significant overall pretest-posttest effect size for WMT for individuals with intellectual disabilities compared to controls [6]. On the other hand, 2 previous meta-analyses on non-pharmacological interventions suggest better evidence for the efficacy of cognitive training is required before these interventions may be labelled as effective interventions for ADHD [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…LD are normally associated with working memory (WM) impairment, most commonly time executive functioning (the function of the central system in WM) (Baddeley, 1986). In fact, several studies have attempted to examine the effect that training WM has on the achievement of students with LD (Gropper, Gotlieb, Kronitz & Tannock, 2014) and any intellectual disabilities they exhibit (Danielsson, Zottarel, Palmqvist & Lanfranchi, 2015). Both of these studies sought to ascertain whether providing specific training on WM tasks improved students' performance in these tasks, and whether any improvement that was identified could be transferred to other WM tasks and to other executive functioning tasks such as reading comprehension tests and students' exam scores.…”
Section: Training Working Memory (Wm) As An Interventionmentioning
confidence: 99%